LAYAKKAH MODEL SHAREHOLDER DAN STAKEHOLDER DITERAPKAN DI INDONESIA? - Eka Fitriani Nikmatul Ulfa; Baihaqi Aksa; Fajar Muhammad Imam Sulaeman (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
Corporate governance is an important thing in succeeding the vision of the mission and the future of the company. The systematic governance of each company varies due to differences in the character and culture of a country. However, each model still has weaknesses so that currently some of the researchers are researching the convergence between corporate governance models.. Therefore, this paper discusses various models of corporate governance such as stakeholder, shareholder and continental models as well as the concept of corporate governance convergence. The purpose of writing this paper first, to know the characteristics of each model as well as how much influence the concept of corporate governance convergence. After successfully exceeding the first goal researchers are also interested to know what is the right corporate governance model to applied on the industry in Indonesia. The method used in writing this paper uses literature studies that use the technique of collecting data library or literature that has been available to be studied and processed as research materials in accordance with the theme.